OPTIMISATION OF SULFURIC ACID CONCENTRATION FOR ENHANCED FE2+ ION REMOVAL USING ACTIVATED CHARCOAL FROM BOILED PEANUT SHELLS: CHARACTERISATION AND PERFORMANCE EVALUATION - Asmara, Anjar; Kamila , Nisaul; Kamila, Nisaul (Lingkar: Journal of Environmental Engineering, 2024)
Groundwater containing iron(II) (Fe2+) ions causes yellowish-brown discolouration and sediment formation. Since bioadsorbents can remove Fe2+ ions, this study investigated the effect of varying H2SO4 activator concentrations (5%, 7%, 9%, 11%, and 13%) on adsorption efficiency and identifies the optimal concentration for activated charcoal derived from boiled peanut shells (Arachis hypogaea L.) to remove the metal ions from well groundwater in Punge Jurong Village in Aceh Province of Indonesia. The process included carbonising the peanut shell waste, activating the charcoal, and testing the adsorbent on well groundwater. The results were analysed using SSA, SEM, and FTIR instruments, along with statistical analysis via SPSS 15 for one-way of analysis of variance (ANOVA). The adsorption efficiencies were 60.43%, 55.53%, 59.01%, 61.81%, 61.94%, and 59.10% corresponding to the activated carbons by H2SO4 (5%, 7%, 9%, 11%, and 13%) and commercial activated carbon, respectively. The IR-assisted characterisation on the boiled peanut shell waste bioadsorbent suggested that wave number shifting on O–H, C=C and C–O typical regions might be due to protonation affect by the acid activator. Conclusively, the study indicates that 13% H2SO4 is the most effective activator concentration for Fe2+ ion removal using activated carbon derived from boiled peanut shells.